Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/ene.12591
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐factor‐bearing microparticles (MPs‐TF) in patients with acute ischaemic stroke: the influence of stroke treatment on MPs‐TF generation

Abstract: Our findings suggest that patients with acute ischaemic stroke have increased generation of MPs-TF. Nevertheless, further studies are needed in order to confirm such inference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Therefore, elevated levels of circulating MPs and TF-loaded cMPs are associated with an increased risk of thrombosis and thromboembolic events. Recently it has been observed that in 73 patients with an acute ischemic stroke, TF-carrying cMPs were elevated compared to healthy individuals [ 26 ], in agreement with our findings. Besides, SMC shed TF-loaded MP with thrombogenic properties in human [ 27 ] and rat aorta [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, elevated levels of circulating MPs and TF-loaded cMPs are associated with an increased risk of thrombosis and thromboembolic events. Recently it has been observed that in 73 patients with an acute ischemic stroke, TF-carrying cMPs were elevated compared to healthy individuals [ 26 ], in agreement with our findings. Besides, SMC shed TF-loaded MP with thrombogenic properties in human [ 27 ] and rat aorta [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…52–54 It has been shown that the level of brain damage is associated with the amount of TF that is released. 55,56 Also ischemic stroke patients have increased TF-bearing microparticles 57 and TF expression on monocytes. 58 …”
Section: Discussionmentioning
confidence: 99%
“…Higher TFMP levels have been demonstrated in patients with acute stroke, stable angina, and acute myocardial infarction (AMI) as compared with healthy subjects. [57][58][59] Conversely, two other studies found that AMI patients had in fact lower TFMP levels than controls. 60,61 These authors hypothesized that adherence of TFMP to the coronary thrombus might lead to a decreased number of circulating TFMP, which is in line with earlier findings of increased levels of TFMP within occluded coronary arteries compared with peripheral blood.…”
Section: Tf-exposing Mp and Arterial Thrombosismentioning
confidence: 99%